Genomic Landscape and Natural History of Sector Retinitis Pigmentosa - Cortinhal, Telmo (2022)
Introduction: Sector retinitis pigmentosa (sRP) is a rare, atypical, and milder variant of rod-cone degeneration. Despite historically associated with RHO gene, the mutational spectrum of sRP is evolving with multiple causative genes recently implicated. This study aimed to characterize the genotypes, phenotypes, and natural history of a Portuguese cohort of sRP.   Methods: Retrospective, observational study, conducted at a tertiary referral center. Patients with a clinical diagnosis of sRP and available genetic testing results were identified using a web-based registry. The clinical diagnosis was established based on ophthalmologic examination, functional testing [best corrected visual acuity (BCVA) and visual field testing] and multimodal imaging [color fundus photography (CFP), fundus autofluorescence (FAF) and optical coherence tomography (OCT)]. Genetic testing was clinically oriented in all probands, and variants were classified according to the American College of Medical Genetics and Genomics. Only likely pathogenic or pathogenic variants were considered disease-causing. Clinical progression was evaluated throughout follow-up. Results: Fourteen patients from twelve families were included. Disease-causing variants in RP-related genes were identified in 8 families, for a diagnostic yield of 66.7%. EYS was the most frequently implicated gene (4 families), followed by RHO (2 families), and finally MYO7A and NPHP1 (1 family each). In most unsolved cases, no clinically significant variants were found. However, for one unsolved case, a RHO-associated variant of uncertain significance was identified. Two patients exhibited syndromic sRP. All cases were bilateral and symmetrical except for two. Inferior and/or nasal retinal involvement on FAF was noted in all cases. Visual field testing revealed superior field defects of varying extents, always in close association with observed FAF findings. Over a median follow-up of 32.5 months (range: 5-148 months), no significant differences were found on BCVA (p=0.056). In fact, BCVA remained stable and ≤ 0.20 LogMAR OU in 9/14 patients. Multimodal imaging revealed no progression over the available follow-up. Conclusion: This study highlights the genotypic heterogeneity of sRP in a Portuguese cohort. Inferior and nasal predilection was common across different genotypes, and a high proportion of patients maintained good central vision. The longitudinal data provided herein will help to accurately inform patients on prognosis.